2004
DOI: 10.1246/bcsj.77.827
|View full text |Cite
|
Sign up to set email alerts
|

Control Crystallization of Calcium Carbonate in Aqueous Solution with In-Situ Radical Polymerization of Sodium Acrylate as a Latent Inductor for Crystal Nucleation and Growth

Abstract: Crystallization of CaCO3 with in-situ radical polymerization of sodium acrylate in aqueous solution was carried out by a double jet method to prevent heterogeneous nucleation at glass walls. The concentration of sodium acrylate was 1.71 mM and the feed ratio of sodium acrylate to calcium ions was 0.62. After addition of the calcium reactants into the aqueous solution of sodium acrylate was completed, an aqueous solution of potassium peroxodisulfate as a water-soluble radical initiator was added to the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…20,31 Furthermore, it was reported that the formation of vaterite was favored under the condition of high pH environment (pH ¼ 10) at room temperature. 32,48 In this work, we found that different CaCO 3 particlesformation mechanisms were formed. All the vaterite products in Table I obtained by the delayed addition of PAA-Na were observed exhibiting the characteristic radiating features, which indicate a spherulitic growth mechanism, as shown in the images of insect and as the arrow indicating in Figure 1.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…20,31 Furthermore, it was reported that the formation of vaterite was favored under the condition of high pH environment (pH ¼ 10) at room temperature. 32,48 In this work, we found that different CaCO 3 particlesformation mechanisms were formed. All the vaterite products in Table I obtained by the delayed addition of PAA-Na were observed exhibiting the characteristic radiating features, which indicate a spherulitic growth mechanism, as shown in the images of insect and as the arrow indicating in Figure 1.…”
Section: Discussionmentioning
confidence: 62%
“…15,32,44 It was found that the stabilizing ability of the vaterite products modified by the higher molecular weights of PAA-Na was stronger than that by PAA1.2k-Na. In the previous report, we proposed that the strong stabilizing effect was attributed to the strong binding strength between PAA-Na and the surfaces of the vaterite particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…acrylate and a water-soluble radical initiator were used for selective interaction with the mineral at different stages during the crystal-forming process. 26 While sodium acrylate does not affect the nucleation and growth of the crystals, poly(acrylate) affects crystal morphology by inhibiting the growth of particular crystal faces. Three different crystal polymorphs of CaCO 3 (aragonite, vaterite, and calcite) were selectively induced by changing the addition time of the radical initiator.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation of CaCO 3 was carried out by a double jet method to prevent heterogeneous nucleation on glass walls, 35 and the sodium salt of PAA was added by a delayed addition method. 26 The effects of different concentrations of calcium reagents were also examined. Although the initial presence of PAA acted as an inhibitor for crystal formation and no crystals were produced, 13,27,29,32 vaterite particles were obtained by the delayed addition of PAA.…”
Section: Introductionmentioning
confidence: 99%